The Social Problem in the Kurdish Novel - Awla, Abdulla R. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2024)
A social problem is the problems and obstacles that appear within the framework of a social situation, affecting human life, thought, and relationships, and passing the problems of human life from one situation to another. Often these new situations that appear as a result of a social problem are not according to the desire of its owner. In this sense, social problems create conditions in which a person suffers himself without his desire. These are circumstances, and with all his weight, he asserts himself upon them and finds a solution and a future for him. In this context, the novel is in relation to other literary genres such as poetry and short stories, and because the narrator‌s space is wide, she can fully represent and prepare for social problems. The novel and its technical preparations can analyze small and large social problems and find appropriate solutions for them. In addition, it clarifies the novelist‌s point of view on social problems and gives the reader the appropriate culture and awareness in many aspects, and the impact of the result directly or indirectly explains the social problems on the individual and groups of society.